Male figure study - hand and clothing - http://id.worldcat.org/fast/1753849 (1935)
An untitled graphite drawing by E. J. Hughes of a man with clothing on and a hand in detail. There is a note that says "Highest Lights" pointing to various parts of the clothing along the man's arm.